Chromosome evolution in fishes: a new challenging proposal from Neotropical species - Nirchio, Mauro; Rossi, Anna Rita; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Sociedade Brasileira de Ictiologia, 2014)
We present a database containing cytogenetic data of Neotropical actinopterygian fishes from Venezuela obtained in a single laboratory for the first time. The results of this study include 103 species belonging to 74 genera assigned to 45 families and 17 out of the 40 teleost orders. In the group of marine fishes, the modal diploid number was 2n=48 represented in 60% of the studied species, while in the freshwater fish group the modal diploid complement was 2n=54, represented in 21.21 % of the studied species. The average number of chromosomes and the mean FN were statistically higher in freshwater fish than in marine fish. The degree of diversification and karyotype variation was also higher in freshwater fish in contrast to a more conserved cytogenetic pattern in marine fish. In contrast to the assumption according to which 48 acrocentric chromosomes was basal chromosome number in fish, data here presented show that there is an obvious trend towards the reduction of the diploid number of chromosomes from values near 2n=60 with high number of biarmed chromosomes in more basal species to 2n=48 acrocentric elements in more derived Actinopterygii.

Se presenta una base de datos que contiene los datos citogenéticos de peces Actinopterigios Neotropicales de Venezuela obtenidos por primera vez en un solo laboratorio. Los resultados de este estudio incluyen 103 especies pertenecientes a 74 géneros de 45 familias contenidas en 17 de los 40 órdenes de teleósteos. En el grupo de peces marinos, el número diploide modal fue 2n=48 representado en 60% de las especies estudiadas, mientras que en el grupo de peces de agua dulce el complemento diploide modal fue 2n=54, representado en el 21,21% de las especies estudiadas. El número de cromosomas y FN promedio fueron estadísticamente superiores en peces dulceacuícolas. El grado de diversificación y variación en el cariotipo también fue mayor en peces de agua dulce en contraste con un patrón citogenético más conservado en peces marinos. En contraposición a la suposición según la cual 48 cromosomas acrocentricos era el número cromosómico basal en los peces, los datos aquí presentados muestran que existe una evidente tendencia hacia la reducción del número de cromosomas desde valores cercanos a 2n=60 con alto número de cromosomas birrámeos en las especies más basales a 2n=48 elementos acrocéntricos en los actinopterigios más derivados.
Keywords: Actinopterygii; Ancestral karyotype; Diploid number; Fundamental number